Pengaruh Digital Marketing, Brand Image, Dan Kualitas Produk Terhadap Keputusan Pembelian Ulang Produk Skincare Lokal Pada Mahasiswa Universitas 17 Agustus 1945 Surabaya - Naomi Maktita; Hotman Panjaitan (Universitas 45 Surabaya, 2023)
The aim of this research is to see the effect of digital marketing, brand image, and product quality on the decision to repurchase local skincare products. All 12,819 students at the 17 August 1945 University of Surabaya became the population of this study. The researcher used purposive sampling in sampling and obtained a sample of 100 respondents from calculations using the slovin formula. Sample collection using questionnaires conducted online and offline with the help of google form. According to the research results obtained multiple linear regression analysis . According to the results of the partial test (t test), partially there is influence from the Digital Marketing (X1), Brand Image (X2), Product Quality (X3) variables on Repurchase Decisions (Y). While according to the F test (simultaneous test) that simultaneously there is influence from the Digital Marketing (X1), Brand Image (X2), Product Quality (X3) variables on Repurchase Decisions (Y).